C.E. Credit. Addressing Access to Care and Bridging the Dental-Medical Services in an Oral Medicine Practice - Sahar Mirfarsi; Aaron Bacha; Vineza Saraza Reduta; Mark Mintline; Craig S. Miller (Taylor & Francis Group, 2023)
ABSTRACTBackground Aging, uninsured, underserved, ethnic/racial minority groups and residents of rural areas are most vulnerable to suffering from a lack of access to health care. These populations experience delays in diagnosis and treatment, making treatment more difficult and expensive.Case Description In as much as the mouth is critical to overall health and quality of life, resources are needed to reduce these disparities and find ways to integrate the practice of dentistry and medicine. The specialty of oral medicine is one venue of opportunity. This paper aims to share the importance of oral medicine specialists in bridging the gap between medicine and dentistry and managing patients using a safety-net dental clinic.Practical Implications The authors present a case that provides insights into "vulnerable" populations, access to care, the importance of early diagnosis, and how safety-net clinics play an important role, especially during the Coronavirus disease 2019 (COVID-19) pandemic, in providing oral health care to a community in need.Continuing Education Credit Available: The practice worksheet is available as supplemental material for this article: https://doi.org/10.1080/19424396.2023.2174659.A CDA Continuing Education quiz is online for this article: https://www.cdapresents360.com/learn/catalog/view/20